Treatment patterns and outcomes for Hodgkin Lymphoma patients aged 60 and older: a report from the Brazilian Prospective Hodgkin Lymphoma Registry - Goveia, Lilian; Castro, Nelson; de Souza, Carmino; Colaço Villarim, Carolina; Traina, Fabiola; Chiattone, Carlos Sergio; Praxedes, Monica; Solza, Cristiana; Perobelli, Leila; Baiocchi, Otavio; Gaiolla, Rafael [UNESP]; Boquimpani, Carla; et al. (Springer Nature, 2023)
The treatment of older patients with Hodgkin lymphoma (HL) remains a challenge. We sought to identify the treatment patterns and outcomes in older HL patients included in the Brazilian HL registry (NCT02589548). A total of 136 patients with HIV-negative classic HL, aged ≥ 60 years, diagnosed between 2009 and 2018, were analyzed. The median age was 66 years old (60-90), 72% had advanced disease, 62% had a high IPS, and 49% had a nodular sclerosis subtype. Median follow-up was 64 months for alive patients. ABVD was the front-line treatment in 96% of patients. Twenty-one patients (15%) died during front-line treatment. The 5-year PFS and 5-year OS rates were 55% and 59%, respectively. The 5-year OS rates in localized and advanced disease were 81% and 51% (p=0.013). Lung toxicity developed in 11% of the patients treated with ABVD. Bleomycin was administered for > 2 cycles in 65% of patients. Compared with 2009-2014, there was a decrease in the use of bleomycin for > 2 cycles in 2015-2018 (88% × 45%, p<0.0001). The impact of socioeconomic status (SES) on outcomes was studied in patients treated with ABVD. After adjusting for potential confounders, lower SES remained independently associated with poorer survival (HR 2.22 [1.14-4.31] for OS and HR 2.84 [1.48-5.45] for PFS). Treatment outcomes were inferior to those observed in developed countries. These inferior outcomes were due to an excess of deaths during front-line treatment and the excessive use of bleomycin. SES was an independent factor for shorter survival.
Keywords: Hodgkin lymphoma; older patients; socioeconomic status; treatment outcomes